Serum KLF5 and CXCL12 levels in patients with chronic obstructive pulmonary disease complicated with type II respiratory failure: Serum KLF5 and CXCL12 levels in COPD with II-RF - Liu, Fangfang; Wang, Na; Sun, Ruru; Fu, Songmin; Chen, Yi; Dong, Pingping (Journal of Medical Biochemistry, 2026)
[Objective] To explore the changes in the serum levels and significance of Kruppel-like factor 5 (KLF5) and chemokine ligand 12 (CXCL12) in individuals suffering from type II respiratory failure (II-RF) in conjunction with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD). [Methods] The observation group consisted of 164 patients with AECOPD and II-RF who were admitted to the hospital between January 2022 and January 2025. There were two groups of patients in the observation group: one with a good prognosis and another with a bad prognosis. The control group consisted of an additional 90 healthy people who were examined physically in the hospital throughout that time. The levels of serum KLF5 and CXCL12 in all research subjects were determined via enzyme-linked immunosorbent assay (ELISA). The associations between the blood levels of KLF5 and CXCL12 in patients with AECOPD combined with II-RF and the associated lung function indicators and the Acute Physiology and Chronic Health Evaluation II (APACHE II) score were examined using Pearson correlation analysis. The predictive value of serum KLF5 and CXCL12 for the prognosis of patients with AECOPD combined with II-RF was analyzed. [Results] Serum KLF5 and CXCL12 levels were substantially higher in the observation group than in the control group (P<0.05). Compared with those in the group with a good prognosis, the levels of serum KLF5 and CXCL12, partial pressure of carbon dioxide (PCO2), and APACHE II score in the poor prognosis group were increased (P<0.05), both the arterial partial pressure of oxygen (PO2) and the forced expiratory volume in one second (FEV1), volume in one/forced vital capacity (FEV1/FVC%), and the percentage of the FEV1%PR to the expected value dropped (P<0.05). FEV1, FEV1/FVC, FEV1%Pred, and PO2 had a negative correlation (P<0.05) with serum KLF5 and CXCL12 levels, whereas PCO2 and the APACHE II score were positively correlated with the levels of serum KLF5 and CXCL12 (P<0.05). The results of the ROC curve analysis revealed that the area under the curve (AUC) for the combined detection of serum KLF5 and CXCL12 for predicting poor prognosis in patients with AECOPD combined with II-RF was 0.947 (95% CI: 0.913–0.981), which was significantly greater than the AUC predicted by the individual detection of KLF5 and CXCL12 [0.870 (95% CI: 0.816–0 923), 0.843 (95% CI: 0.770–0.915)], and the differences were statistically significant (Z = 2.413, P = 0.016; Z = 2.554, P = 0.011). [Conclusion] The levels of serum KLF5 and CXCL12 in patients with AECOPD combined with II-RF were significantly increased. Additionally, detecting both of these indications together offers a good prognostic value for the poor prognosis of patients with II-RF and AECOPD. Therefore, serum KLF5 and CXCL12 can be used as serum markers for predicting the poor prognosis of patients with AECOPD combined with II-RF. Guide clinical diagnosis and treatment.